Ca2+-permeable AMPA receptors in homeostatic synaptic plasticity - Lee, Hey-Kyoung (Frontiers in Molecular Neuroscience, 2012)
Neurons possess diverse mechanisms of homeostatic adaptation to overall changes in neural and synaptic activity, which are critical for proper brain functions. Homeostatic regulation of excitatory synapses has been studied in the context of synaptic scaling, which allows neurons to adjust their excitatory synaptic gain to maintain their activity within a dynamic range. Recent evidence suggests that one of the main mechanisms underlying synaptic scaling is by altering the function of postsynaptic α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors (AMPARs), including synaptic expression of Ca2+-permeable (CP-) AMPARs. CP-AMPARs endow synapses with unique properties, which may benefit adaptation of neurons to periods of inactivity as would occur when a major input is lost. This review will summarize how synaptic expression of CP-AMPARs is regulated during homeostatic synaptic plasticity in the context of synaptic scaling, and will address the potential functional consequences of altering synaptic CP-AMPAR content.